2016
DOI: 10.3141/2551-12
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Effects of Precipitation on Vehicle Speed: Floating Car Data Approach

Abstract: Extreme precipitation as a result of the ongoing change of climatic conditions is attributed to significantly hindering vehicle circulation in urban transportation networks. During 2014, Thessaloniki, Greece, experienced significant anomalies with respect to the expected amount and intensity of rainfalls, which severely influenced traffic flow and safety conditions. According to the National Meteorological Service, a 360% deviation in the total rainfall accumulation (compared with the 1959–1997 mean) was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…When evaluating the effect of weather change on vehicles’ speed drop, the popular method used in the literature is regression and trend analysis [ 7 , 15 , 25 , 26 ]. Camacho et al [ 7 ] modeled the traffic speed of 15 major freeways in northern Spain using regression analysis based on several indicators: number of trucks, visual visibility, wind speed, precipitation intensity, and snow thickness.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…When evaluating the effect of weather change on vehicles’ speed drop, the popular method used in the literature is regression and trend analysis [ 7 , 15 , 25 , 26 ]. Camacho et al [ 7 ] modeled the traffic speed of 15 major freeways in northern Spain using regression analysis based on several indicators: number of trucks, visual visibility, wind speed, precipitation intensity, and snow thickness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They found that different rainfall intensity affects traffic flow, as summarized in Table 1 . The regression and analysis approaches were also used by Mitsakis et al [ 25 ] and Stamos et al [ 26 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Fog may increase drivers’ perceived distance compared with that under prevailing conditions ( 3 ), which would increase vehicle headway, reduce road capacity and speed, and increase speed variation ( 4 7 ). Rain reduces visibility and sight distance in addition to decreasing road surface friction ( 8 , 9 ).…”
Section: Literature Reviewmentioning
confidence: 99%